Book Review: Guide of Good Practices Regarding the Preparation of Graduation Theses for Bachelor and Master’s Degree Cycles. Author: Vasile Dinu - Dumitru Miron (Amfiteatru Economic)
The role of a teacher is to provide his disciples with professional knowledge and guidance, to contribute to the configuration of their cognitive skills, to guide them in the process of selecting what is valuable and useful, and to shape characters. A scholar once said that “The task of the modern educator is not to cut down jungles, but to irrigate deserts” (Lewis, 2014). This is the true role of quality education, carried out by dedicated trainers, who have the vocation of a job well done and did not get lost in the educational landscape, but had a real calling for it. The modern teacher in higher education who serves the valuable field of economics must be a facilitator of vocational training processes, demonstrate the ability to make students integrate the knowledge they have access to and not only accumulate information about a particular field of advanced knowledge, but to know what to do with them, by understanding why economic phenomena and processes occur in that way and not otherwise.